2017
DOI: 10.1002/cncy.21947
|View full text |Cite
|
Sign up to set email alerts
|

High‐grade urothelial carcinoma in urine cytology with jet black and smooth or glassy chromatin

Abstract: BACKGROUND: Some high-grade urothelial carcinomas (UCs) in urine cytology can have jet black, smooth, or glassy chromatin, but to the authors' knowledge, the incidence and criteria for diagnosis are not well described. The current study was performed to define the incidence and appearance of high-grade UC in urine cytology in cytospin preparations with jet black and smooth or glassy chromatin. METHODS: Cytospin preparations from 331 cases with biopsy follow-up (230 benign/low-grade UCs and 101 malignant UCs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Moreover we suggest that the absence of hyperchromasia could not preclude a diagnosis of HGUC, in cells having a very large nucleus, nuclear to cytoplasm ratio (N/C) >0.7, irregular nuclear membranes, coarse chromatin and macronucleoli. It has been seen that urothelial high grade carcinoma has multiple different cytological patterns and when strictly applying a single set of diagnostic criteria, some cases will be overlooked .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover we suggest that the absence of hyperchromasia could not preclude a diagnosis of HGUC, in cells having a very large nucleus, nuclear to cytoplasm ratio (N/C) >0.7, irregular nuclear membranes, coarse chromatin and macronucleoli. It has been seen that urothelial high grade carcinoma has multiple different cytological patterns and when strictly applying a single set of diagnostic criteria, some cases will be overlooked .…”
Section: Discussionmentioning
confidence: 99%
“…However, decoy cells and malignant urothelial cells can co‐exist as shown in cases described in Table . Occasionally, HGUC cells can have features like jet black and smooth or glassy chromatin similar to decoy cells . Often a difficult task, the distinction could be made based on the cellularity and the nuclear membrane irregularity .…”
Section: Discussionmentioning
confidence: 99%
“…16,21,24 Occasionally, HGUC cells can have features like jet black and smooth or glassy chromatin similar to decoy cells. 45 Often a difficult task, the distinction could be made based on the cellularity and the nuclear membrane irregularity. 45 Table 2 summarizes the cytologic features helpful in the differential diagnosis between degenerated urothelial cells, decoy cells and malignant urothelial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the machines will use similar criteria. From our experience and that of others, humans can make the diagnosis in absence of these criteria. For example, although the N/C ratio and nuclear hyperchromasia are very important features used (by humans) to make a diagnosis of urothelial carcinoma, our morphometric analysis of cases has shown that a small percentage of these cases have hypochromatic nuclei or lower nucleocytoplasmic ratios.…”
mentioning
confidence: 99%